THE EFFECTS OF QURAN RECITATION ON IMPROVING UNIVERSITY STUDENTS’ ATTENTION - Safrilsyah, Safrilsyah; Yasa, Rawdhah binti; Misnawati, Misnawati; Aliana, Cut Rizka; Maghfirah, Muthia; Zakaria, Norazlina binti (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2024)
Attention which is achieved through the process of adapting to new conditions and information can be an issue for new students. Previous studies have suggested that listening to Quran recitation (murattal) can positively influence attention. Therefore, this study aims to investigate the effects of listening to Quran recitation on students’ attention. The research was conducted by designing a quasi-experiment with a non-randomized pre-test and post-test control groups. Besides this, the groups were divided into two, the experimental group and the control group. The data were collected from 20 new students of Ar-Raniry State Islamic University as a sample, who met the criteria of having healthy hearing conditions and obtained GPA > 3.50. The measuring instrument utilized in the study was the number range test of Weschler Intelligence Scale, while the treatment used was listening to Quran recitation. Then, the data was analyzed using a paired t-test to examine the difference in attention between the experimental group and the control group. The results showed that there was a difference in the average attention score between the experimental group of 11.70, and the control group of 8.80 with a significance level of 0.026 (P < 0,05). Thus, the findings of the study indicate that there is a significant difference in attention between the experimental group and the control group after listening to Quran recitation.